Penerapan Komunikasi ESP-NOW dengan Topologi Jaringan Mesh Sebagai Bentuk Interoperability dalam Konsep Network Centric Warfare - Mardamsyah, Adam; Winandika Saragih, Gabriel; Farras Zhafran, Ariq; Simanjuntak, Ian Rosi; Riadi, M. Farrel (Mahesa Research Center, 2024)
Network-centric warfare (NCW) is a concept that prioritizes integration and interconnection between combat elements to improve operational effectiveness. One approach to achieve high interoperability is ESP-NOW communication with mesh network topology. ESP-NOW technology enables fast and efficient wireless communication between devices without Wi-Fi infrastructure or routers. This research implements a mesh network topology using ESP32 modules that support ESP-NOW, where each node can function as a repeater to facilitate communication between devices beyond direct range. Reliability and network coverage testing was conducted by measuring latency and throughput parameters, which showed an average latency of 15 ms and a throughput of up to 2 Mbps, sufficient to support tactical communications in real-time. Although the performance is satisfactory, the obstacles encountered include limited coverage in dense environments and signal interference, which affects the stability of the connection. The study illustrates how the integration of ESP-NOW with mesh improves interoperability within NCW, allowing military units to share real-time data, such as position coordination, situational information, and operational commands. Thus, this implementation has great potential in future military operations, strengthening the integration of combat units and situational awareness on the battlefield.